Dental Caries in Preschoolers and Parental Level of Oral Health Literacy in Tocantins - da Silva Benigno, Marlon Brendo; da Silva, Juliana Bastoni; Avila, Marla Andreia Garcia de; Nunes, Helio Rubens de Carvalho; Mialhe, Fábio Luiz (FapUNIFESP (SciELO), 2025)
ABSTRACT Objective: To investigate the association between dental caries in preschoolers and parental oral health literacy (OHL) levels. Material and Methods: A cross-sectional study was conducted with 448 dyads of five-year-old preschoolers in all public preschools in the urban area of Porto Nacional city (Tocantins, Brazil) and their respective primary caregivers. Caries experience with deciduous teeth was measured through the decayed, missing, and filled teeth (dmft) index. OHL level was calculated using the Brazilian Portuguese version of the Health Literacy in Dentistry (HeLD-14) instrument and categorized into tertiles. Sociodemographic data were collected. Associations between variables were evaluated by Poisson’s regression in bi and multivariate models. Results: A total of 190 (42.41%) children had dental caries in at least one tooth, and 243 (54.2%) of the primary caregivers showed an OHL level below the sample median (49 points). Analyses revealed that an OHL level at the upper fertile was considered a protective factor for caries in the evaluated preschoolers (RP=0.660; 95% CI = 0.480-0.910). Conclusion: Parental oral health literacy level was significantly associated with early childhood caries. Promoting oral health literacy among parents can be important in preventing tooth decay in preschoolers.